Maternal and neonatal outcome in primigravida with mobile head at ≥39 weeks of gestation - C., Sadhanadevi; B., Sajini; Varghese, Acka Priya; Raju, Divya Sara; Kurup, Karishma Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Primigravida with mobile head at ≥39 weeks of gestation are prone to the probability of caesarean section. With this study we aimed to identify the maternal and neonatal outcome of primigravida with mobile head at ≥39 weeks of gestation under the watchful expectancy and good conduct of labour. Methods: A cross sectional study was conducted among primigravida with mobile head at ≥39 weeks admitted for delivery in the department of obstetrics and gynaecology, govt. medical college, Kottayam, Kerala, from February 2021 to September 2021. A sample size of 247 was identified considering 28% proportion of presentation with deflexed head, 95% confidence interval and 2% margin of error. A detailed history, physical examination and ultrasonography was performed. Results: Of the 250 participants, the mean age of the study subjects was 24.97±3.93 and mean body mass index (BMI) was 23.72±4.78 kg/m2. The most common cause for mobile head was a deflexed head (35.2%). A lower segment caesarean section (LSCS) was conducted in 28.8% participants while vacuum assistance ad forceps assistance was required for 9.6% and 4.4% participants respectively. The most common indication for LSCSC being moderate to thick meconium-stained amniotic fluid (MSAF) 23% followed by 1st degree CPD failed trial in 17% cases. A significant association with maternal morbidity was observed in undiagnosed placenta previa (p=0.039) and vacuum-assisted deliveries (p=0.001). We observed that 3.6% of babies have meconium aspiration syndrome, and 8% of new born were admitted in intensive care for foetal distress. Conclusions: Primigravida with mobile head at term during labour requires intense monitoring. Although the duration of labour appeared to be prolonged in a small proportion of patients with watchful expectancy and good conduct of labour and timely intervention, vaginal delivery is possible with minimal maternal and neonatal morbidity.